The Evolution Usefulness Scale: Development, Reliability, and Validity - SALMAN, Muhammed; GÜVEN, Turan (Kastamonu Egitim Dergisi, 2021)
Purpose: The aim of the current study was to develop a scale to measure the perceived usefulness of the evolutionary theory among biology students who are pre-service teachers. Design/Methodology/Approach: Firstly, the related literature was analysed to compose a scale, and then the item pool was constructed. The pilot form of the scale was administered to the biology teacher candidates, and the factorial structure and reliability were analysed via explanatory factor analyses and Cronbach’s Alpha coefficient. Then, the final form of the scale was composed based on the results of the pilot testing. The study group of the research included 222 biology teacher candidates. Explanatory and confirmatory factor analyses were conducted to obtain proof on construct validity. Findings: As a result of these analyses, it was decided that the scale has a unidimensional structure with 58.6% explained variance. As for reliability, Cronbach’s Alpha coefficient was estimated, and it was found as .94, which indicates a high level of inter-consistency. At the end of the study, it was concluded that the Evolution Usefulness Scale (EUS), which includes 13 items, can measure the perceived usefulness of the theory of evolution in a valid and reliable manner. Highlights: It is thought that developing a scale that will determine whether the theory of evolution is useful in understanding other biology topics will fill the gap in the field.
Keywords: Eğitim Üzerine Çalışmalar; Studies on Education; The theory of evolution; Scale development; The usefulness scale; Biology education; Evrim teorisi; Ölçek geliştirme; Yararlılık ölçeği; Biyoloji eğitimi